Controle externo e Policy Making? Uma análise da atuaç\~ao do TCU na administraç\~ao pública federal - Eduardo José Grin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– The main objective of this work is to analyze how the Brazilian Supreme Audit Institution (Tribunal de Contas da Uni\~ao - TCU) has been acting in the policy making of the federal public administration. It seeks to highlight that in addition to the classic functions of a court of accounts that oversees governmental acts, there has been an expansion of performance aimed at evaluating the performance and implementation of public programs and policies. The text highlights that there are several factors that affect this change in trajectory that gives the Court's operational audits a prominent place alongside those that are more focused on the analysis of legal and formal compliance. The international literature highlights that changes in the roles of the courts of accounts have been deepening in several countries. A second group of factors considers the so-called "good practices": experiences of countries taken as examples (especially the United States and England) and international organizations that disseminate ways of acting (Organisation for Economic Co-operation and Development - OECD, International Organization of Supreme Audit Institutions - Intosai, United Nations - UN and World Bank). The research analyzes the Court's organizational structure, such as salaries and schooling of civil servants, in which it finds that both are higher than the average for the Executive, Legislative and Judiciary branches. The investigation examines how the official documents of the TCU appropriate the international debate, and the support on the Federal Constitution, which underlies the expansionism of its actions. This debate upholds the analysis of three empirical evidence capable of discussing this argument. Initially, backed on audit database created after a search on the court's website. Operational audits were identified that, since 2005, have been expanding TCU's performance in several public policies. Also were analyzed the Inspection Reports on Government Policies and Programs and Systemic Inspection Reports. Since 2005, there has been a significant expansion of audits aimed at evaluating public policies. In order to thicken the research, interviews were carried out with six TCU external control departments, aiming to present how this kind of acting is institutionally justified. The comparison with the literature, the document analysis that underlies this form of action, the alignment with the international "epistemic community" and the features of its organizational structure allow us to understand how external control justifies and validates its activities into the policy making of public administration. The conclusions summarize this process within the scope of public management and its managerial and political effects. Research agendas are suggested seeking to increase this incipient field of study in the areas of public administration and political science in Brazil.
Keywords: H83; 330; performance audit; external control; public policy; TCU